Recollection and familiarity components of recognition: effect of side of mesio-temporal damage. Issue 1 (2nd January 2016) - Lombardi, Maria Giovanna; Fadda, Lucia; Serra, Laura; Di Paola, Margherita; Caltagirone, Carlo; Carlesimo, Giovanni Augusto
Abstract : We investigated the memory performance of three patients with unilateral mesio-temporal lobe damage with the aim of evaluating the roles of the left and right hemispheres in recollection and familiarity. Consistent with the "Material Specificity Hypothesis", the right brain-damaged individual was selectively poor on recollection and familiarity tests for faces. Conversely, left-lesioned patients were severely deficient in recollection and familiarity of verbal material but mildly deficient on visual-spatial tests. This partially unexpected finding is interpreted in light of the ability of humans to verbally recode almost any material, thus giving rise to left-hemisphere effects for nominally nonverbal stimuli.